Pembentukan Karakter Religius Santri dalam Kegiatan Mujahadah - Badriyan, Mokhamat Khadik; Hidayat, Nur; Daheri, Mirzon (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose - The formation of religious character is vital for individual growth as it significantly influences attitudes, words, and actions. The religious character embodies moral values in daily actions, with its pinnacle being steadfastness in adhering to religious teachings. One impactful religious activity contributing to character development is mujahadah, oriented to draw closer to Allah SWT and foster steadfastness in obeying religious commands. This research delves into mujahadah activities, extending beyond a focus on religious rituals and serving as a comprehensive learning process for students to cultivate their religious character. Methods - Utilizing the library research method, the study explores literature related to the research topic for data collection, employing a qualitative approach where data consists of written words. The process includes data collection from library sources, reading, note-taking, and material processing. Findings - The findings underscore the significant role of mujahadah activities in shaping students' religious character and positively influencing attitudes and personalities. The research concludes that mujahadah is not just a daily routine; rather, it emerges as a highly effective method for character development in the pesantren environment. This holistic process involves spiritual, social, and psychological aspects synergistically, shaping individuals to exhibit steadfastness in their religious beliefs while being independent and responsible. Research Implications - The implication is that Pondok Pesantren can optimize mujahadah activities to shape the religious character of students, implementing education strategies rooted in Islamic values for improved character formation in the pesantren environment.